2019
DOI: 10.1111/jfpe.13201
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost healthy extrudates of rice and bhimkol (Musa balbisiana, ABB) formulated through linear programming

Abstract: Low amylose rice, intermediate amylose rice, and seeded banana were taken for formulation of an extruded product using linear programming (LP) model. The model was designed to develop nutritious low‐cost extrudate products. The optimization for development of extrudates was performed by using central composite rotatable design (CCRD). The formulated extruded product developed at the optimized condition was found to have calorific value of 175 kcal/100 g and protein content of 6.35% with adequate amount of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Low-amylose rice could be utilized to develop extrudates with better physicochemical properties [ 6 ]. Borah et al [ 7 ] reported honeycomb structure and better pasting properties for extruded weaning food formulation developed using low-amylose rice. Therefore, the plan of this research is to remove the high amylose content of red adzuki bean starch by using warm water modification to make it more amenable [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-amylose rice could be utilized to develop extrudates with better physicochemical properties [ 6 ]. Borah et al [ 7 ] reported honeycomb structure and better pasting properties for extruded weaning food formulation developed using low-amylose rice. Therefore, the plan of this research is to remove the high amylose content of red adzuki bean starch by using warm water modification to make it more amenable [ 2 ].…”
Section: Introductionmentioning
confidence: 99%